Health-related quality of life and disease activity in rheumatoid arthritis: a cross-sectional study in West Java, Indonesia - Ausi, Yudisia; Sinuraya, Rano K.; Dewi, Sumartini; Barliana, Melisa I.; Postma, Maarten J.; Suwantika, Auliya A. (Frontiers in Medicine, 2025)
BackgroundJoint inflammation is a key manifestation of rheumatoid arthritis (RA), often leading to functional limitations and reduced quality of life (QoL) as the disease progresses. This study aims to examine the association between disease activity and health-related quality of life (HRQoL) in RA patients.MethodsA cross-sectional study was conducted among 110 RA patients aged 18–65, diagnosed according to the 2010 ACR/EULAR criteria and receiving disease-modifying antirheumatic drugs (DMARDs) therapy for at least 1 month. Patient data were obtained from electronic medical records and verified through structured interviews. Health-related quality of life (HRQoL) was assessed using the EQ-5D-5L questionnaire, while disease activity was measured using the DAS28-ESR. Non-parametric analysis was performed to compare EQ-5D scores based on patient characteristics.ResultThe most frequently reported problem was pain/discomfort (76.36%), showing significant differences across disease activity groups. Other commonly affected dimensions included usual activities (46.36%), anxiety/depression (44.55%), mobility (33.64%), and self-care (19.09%). The mean EQ-5D index was 0.76 (95% CI, 0.73–0.80), and the visual analogue scale (VAS) score was 73.05 (95% CI, 69.91–76.19). Disease activity and comorbidity showed a statistically significant association with HRQoL (p = <0.001; OR = 6.33; CI 95% 2.29–17.51 and p = 0.005; OR = 3.65; 95% CI 1.50–8.93, respectively).ConclusionThis study suggests that higher disease activity and comorbidity were negatively associated with HRQoL among RA patients. Disease progression disrupts multiple dimensions of quality of life of the subjects. This study highlights the importance HRQoL assessments in RA management to ensure a more comprehensive approach to patient care.